(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the small life cycle of perennial cereals in the adyr zones of the Republic of Uzbekistan. As a result of the analysis of the results obtained, it was noted that the maximum lifespan of the maternal shoot (p+I) in Agropyron cristatum and Hordeum bulbosum is 25-26 months, and in Elytrigia trichophora up to 4 years. In Hordeum bulbosum, the first and second shoots p+2 die off along with the mother shoot, i.e. Their lifespan is 10-18 months. In Agropyron cristatum, the 1st and 2nd shoots p+2 remain viable for two years, and in Elytrigia trichophora for 3-4 years.